Pds5A and Pds5B Display Non-redundant Functions in Mitosis and Their Loss Triggers Chk1 Activation - Al-Jomah, Naif; Mukololo, Lubinda; Anjum, Awais; Al Madadha, Mohammed; Patel, Raj (Frontiers in Cell and Developmental Biology, 2020)
Background: Pds5 is an abundant HEAT-repeat-containing protein that interacts with the cohesin complex and mediates sister chromatid cohesion. In vertebrates, Pds5A and Pds5B are known to regulate the dynamic behavior of cohesin and protect DNA replication fork, as their loss leads to DNA damage. Pds5 interacts directly with the cohesin release factor, Wapl, to remove cohesin during mitosis. Aim: To analyze the effects of the loss of Pds5 proteins-mediated DNA damage on the cell cycle checkpoints and to examine the possibility that Pds5 proteins have an overlapping function. Methodology: We first analyzed the cell cycle regulation of Pds5 proteins and defects in S-phase; DNA damage was confirmed after Pds5A/B knockdown. The activation of cell cycle checkpoints and apoptosis were examined by the level of p-Chk1S317, MAD2 localization, and the level of pro-apoptotic markers, respectively. Results: Pds5 proteins dissociated from chromatin in a stepwise manner, and their loss led to an increased level of Smc3 acetylation and pro-apoptotic markers associated with the phosphorylation of Chk1S317 due to DNA damage. The depletion of both Pds5 proteins severely impaired Smc3 acetylation. Moreover, the loss of Pds5A/Pds5B activated the SAC in an ATR-Chk1-dependent manner without affecting Wapl recruitment to the chromatin. The depletion of Chk1 rescued the S phase delay associated with the depletion of Pds5 and significantly increased mitotic catastrophe. Conclusion: Pds5A and Pds5B display overlapping functions in facilitating Smc3 acetylation. Somewhat paradoxically, they also have non-redundant functions in terms of cohesin removal due to the activated surveillance mechanism that leads to phosphorylation of Chk1S317.